State Water Agencies in Nigeria : A Performance Assessment - Macheve, Berta; Danilenko, Alexander; Abdullah, Roohi; Bove, Abel; Moffitt, L. Joe (Washington, DC: World Bank, 2015)
Investments on the order of $US6 billion are estimated to be needed in the water sector in Nigeria in the next 10 years if the country is to achieve universal water supply coverage. This is the main finding of State Water Agencies in Nigeria: A Performance Assessment. The report focuses on water provision services from the state water authorities (SWAs), or water boards, as they are the major and only regulated agencies that provide water to the urban population. Sanitation provision is not addressed because the majority of SWAs do not provide this service to their customers.